Deployment of PIM guidance on development of multi-actor platforms for landscape governance and restoration across six states in India - CGIAR Research Program on Policies, Institutions, and Markets (2020)
With support from PIM, Collaborating for Resilience worked with Foundation for Ecological Security (FES) to develop guidance and train FES field teams on development of multi-actor platforms for landscape-level governance and restoration efforts in India. The guidance has been adopted as an integral part of Foundation for Ecological Security’s program implementation across six states (Andhra Pradesh, Gujarat, Karnataka, Odisha, Rajasthan and Uttar Pradesh).